2015
DOI: 10.1007/s00253-015-6488-2
|View full text |Cite
|
Sign up to set email alerts
|

pH regulates ammonia-oxidizing bacteria and archaea in paddy soils in Southern China

Abstract: Ammonia-oxidizing archaea (AOA) and bacteria (AOB) play important roles in nitrogen cycling. However, the effects of environmental factors on the activity, abundance, and diversity of AOA and AOB and the relative contributions of these two groups to nitrification in paddy soils are not well explained. In this study, potential nitrification activity (PNA), abundance, and diversity of amoA genes from 12 paddy soils in Southern China were determined by potential nitrification assay, quantitative PCR, and cloning.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(28 citation statements)
references
References 52 publications
(62 reference statements)
4
24
0
Order By: Relevance
“…As Jing [27] observed, the increase in pH from 4.4 to 6.4 resulted in an increase of archaeal amoA gene abundance in paddy soil. These results were further supported by a study on paddy soils from southern China, showing that AOA abundance significantly increased with increasing pH in acidic and neutral paddy soils [25]. Taken together, however, these results seem to suggest that while both groups benefit from moderate conditions, relatively favorable edaphic conditions, i.e., neutral pH and an abundance of nutrients, seem to benefit bacteria disproportionately.…”
Section: Nitrogen Fertilizer and Phsupporting
confidence: 68%
See 3 more Smart Citations
“…As Jing [27] observed, the increase in pH from 4.4 to 6.4 resulted in an increase of archaeal amoA gene abundance in paddy soil. These results were further supported by a study on paddy soils from southern China, showing that AOA abundance significantly increased with increasing pH in acidic and neutral paddy soils [25]. Taken together, however, these results seem to suggest that while both groups benefit from moderate conditions, relatively favorable edaphic conditions, i.e., neutral pH and an abundance of nutrients, seem to benefit bacteria disproportionately.…”
Section: Nitrogen Fertilizer and Phsupporting
confidence: 68%
“…Finally, the third grouping includes the results of three studies with extremely high AOA/AOB ratios, above 300. As can be seen, two of these studies have acidic soils [10,25], whereas the other has a relatively alkaline soil with high levels of ammonium [23]. Table 1).…”
Section: Nitrogen Fertilizer and Phmentioning
confidence: 99%
See 2 more Smart Citations
“…Nicol et al (2008) confirmed that soil pH determined the phylotype distribution of bacterial and archaeal ammonia oxidizers. Li et al (2015) also reported that the ammonia oxidizers community structure and nitrification activity were significantly affected by soil pH. The aim of our work was to investigate the short-term effects of nitrapyrin and NBPT on nitrification and the abundance and community structure of AOA and AOB in a vegetable soil across a pH-gradient.…”
Section: Introductionmentioning
confidence: 92%